"Transporting the notes:" urbanization and westernization in the music of the northeastern Aegean islands in the nineteenth and the twentieth century. (3rd July 2019) - Dalianoudi, Renata
ABSTRACT: The music of the North Aegean Sea Islands between Europe and Asia has undoubtedly been influenced by neighbouring cultures. The syncretic melding of disparate strands has also formed an indigenous, cosmopolitan cultural identity in the North Aegean Sea islands, comprising Lesbos, Limnos, Ai Stratis, Chios, Oinousses, Psara, Samos, Ikaria and Fourni. Identity emerges from mythical and historical events, including indigenous Greek, Oriental and Western ethnic materials of continental and island origins. Adopting an interdisciplinary methodology crossing historical ethnomusicology and musicology, cultural anthropology and the sociology of music, this paper presents results of ethnographic research into music and dance. It explores identity formation from the late nineteenth century to the present. It focuses on changes in musical practices, performance, education, repertoire and lifestyle. Centralizing policies emanating from Athens combined with social and technological changes mark transitions from local to European, from eastern to western style, providing a context for urbanization and westernization.